47. ASSESSMENT OF THE FLUCTUATION OF ANTI SARS-COV-2 IGG CONCENTRATION IN VACCINATED PEOPLE, APPLICATION IN COVID-19 PREVENTION (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the clinical characteristics of vaccinated people and study the changes in anti-SARS-CoV-2 IgG levels in people vaccinated with the COVID-19 vaccine.Research subjects and methods: Cross-sectional descriptive study divided into 3 time points: T6 (6 months after vaccination: 400 people); T12 (12 months after vaccination: 404 people); T18 (18 months after vaccination: 411 people) on people after vaccination with CoVid-19, the medical staff of hospitals in Hanoi and volunteers participating in the study.Results: Regarding vaccine type: the 1st and 2nd doses of all 3 groups were mainly injected with Astrazeneca vaccine, and the 3rd and 4th doses of groups T6, T12, and T18 were mainly injected with Pfize vaccine. Regarding blood type, all 3 groups had the highest rate of blood type O+ at 43.8%, 46%, and 41.6%, respectively. Regarding the number of vaccinations, groups T6 and T12 have the highest rate of 4 vaccinations at 66.3% and 82.17%, respectively; group T18 has the highest rate of 3 vaccinations at 58.6%. Antibody concentration: group T6 has the highest antibody concentration with a median of 299.78 IU/ml, group T12 has a lower antibody concentration with a median of 162.33 IU/ml, and group T18 has the lowest antibody concentration with a median of 98.19 IU/ml.Conclusion: Group T6 BMI: underweight and obese groups had significantly lower antibody concentrations; Antibody concentrations decreased over time, highest in the 6-month postvaccination group and lowest in the 18-month post-vaccination group.
Keywords: Covid 19; anti-SAR CoV-2 IgG; vaccines; Son Tay General Hospital